Citric Acid‐Crosslinked Highly Porous Cellulose Nanofiber Foam Prepared by an Environment‐Friendly and Simple Process. Issue 11 (2nd September 2022) - Dinesh,; Wang, Hanbin; Kim, Jaehwan
Abstract: In this study, cellulose nanofiber (CNF) foams are prepared by an environment‐friendly, time‐saving, and simple process using bio‐based citric acid (CA) as a green crosslinking agent. Scanning electron microscope and Fourier transform infrared spectroscopy examine the foam morphology and confirm the crosslinking. The prepared foam shows a very high porosity (>98%) with a low density (24.02 mg cm −3 ) with more than 200% improvement in mechanical strength and modulus compared to the neat CNF foam. In addition, the inclusion of CA into CNF improves thermal stability, antioxidant activity, and hydrophobicity. Furthermore, the prepared foam demonstrates a good sound absorption behavior, suitable for environment‐friendly and lightweight sound‐absorbing foam. Abstract : Using citric acid, a biobased green crosslinking agent, highly porous, low‐density cellulose nanofiber (CNF) foams are prepared by a simple, environmentally friendly, time‐saving, and economical process. The prepared citric acid‐crosslinked CNF foams exhibit high mechanical and antioxidant properties, good thermal stability, and good sound‐absorbing properties for promising environment‐friendly sound‐absorbing and packaging applications.